Pseudomonas aeruginosa-innoculated MFC to increase power generation. - Koh, Jieshi. (2012)
Renewable bioenergy is being deemed as one of the possible solutions to slow down global warming crisis, besides the conventional alternatives like expensive Solar and Wind energy. MFC is an instrument which converts organic matter into electricity with the use of bacteria. Bacteria Pseudomonas aeruginosa thrives in both normal and hypoxic atmospheres; feeds on a diverse range of organic materials, including glucose, lactate, cellulose and even toxics such as phenol [5]. This report focuses on the use of Pseudomonas aeruginosa in Microbial Fuel Cell. There are 2 projects elaborated in the report. The first project (Training project) attempts to find out if Pseudomonas aeruginosa is able to degrade harmful toxic phenol under anaerobic conditions to generate useful electricity. The second project is on how overexpression of quorum sensing system in Pseudomonas aeroginosa enhances bioelectricity in the MFC. Pseudomonas aeruginosa is one of the many species of bacteria that use quorum sensing to coordinate gene expression according to the density of their local population. By manipulating the genetic regulatory system, the bacteria’s metabolisms are altered and induce more production of efficient shuttles. In particular, the overexpression of a particular quorum sensing system enhances power output of P.aeruginosa inoculated MFC via the synthesis and switching to a more efficient electron transfer shuttle. The increase in power generation efficiency will bring about significant improvement in on many MFC researches and processes.